Histologic and histomorphometric evaluation of the effect of lactoferrin combined with anorganic bovine bone on healing of experimentally induced bony defects on rabbit calvaria - Mojgan Paknejad; Amir Reza Rokn; Ali Akbar Sabur Yaraghi; Flora Elhami; Mohammad Javad Kharazifard; Neda Moslemi (Wolters Kluwer Medknow Publications, 2012)
Background: Recent studies have shown that lactoferrin promotes the proliferation and differentiation of osteoblasts and inhibits osteoclast-mediated bone resorption. Anorganic bovine bone (ABB) graft has been extensively used as an osteoconductive material in the bone reconstructive surgeries. The purpose of this study was to examine whether the combination of lactoferrin with Bio-Oss would improve ossification in experimentally induced bone defects in rabbit calvaria. Materials and Methods: In this randomized, prospective animal study, a total of 32 bone defects with the diameter of 6 mm were created on the calvaria of 8 male New Zealand rabbits (4 defects in each animal). One defect was filled with ABB + Lactoferrin + Vehicle (BLV), the second one with ABB + Lactoferrin (BL), the third defect with ABB + V (BV), and the fourth defect was filled with ABB (B) alone. After 4 weeks, histologic sections were prepared and evaluated histologically and histomorphometrically. The type, percentage and vitality of newly formed bone, inflammation, percentage of residual material, and foreign body reaction were assessed for each specimen. Data were analyzed using Friedman tests. Results: All groups were similar in terms of inflammation and vitality, type, percentage of new bone formation, and residual material. The percentage of new bone formation in BLV, BL, BV, and B groups were 14.73 ± 3.14%, 15.02 ± 1.51%, 15.95 ± 2.24% and 13.44 ± 2.89% ( P = 0.1) and the amount of residual biomaterial were 11.85 ± 1.50%, 13.73 ± 1.80%, 13.02 ± 1.86%, and 15.41 ± 2.05%, respectively ( P = 0.392). Conclusion: Based on results of this study, the combination of lactoferrin and ABB did not show any significant improvement in bone regeneration compared with ABB alone in surgically induced bony defects in rabbit calvaria.